2015
DOI: 10.1016/j.carpath.2014.08.005
|View full text |Cite
|
Sign up to set email alerts
|

JNK is critical for the development of Candida albicans-induced vascular lesions in a mouse model of Kawasaki Disease

Abstract: Our findings suggest that JNK is crucial for the development of CAWE-induced vascular lesions in mice, and potentially represents a novel therapeutic target for KD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…Of interest, a recent study using the Candida albicans extract-induced KD vasculitis mouse model also reported the development of systemic artery lesions in addition to coronary lesions 55 . Together, these observations suggest that in children with KD the incidence of AAA and dilation may be higher than currently appreciated, particularly in infants less than one year of age with very severe KD vasculitis and coronary aneurysms.…”
Section: Discussionmentioning
confidence: 99%
“…Of interest, a recent study using the Candida albicans extract-induced KD vasculitis mouse model also reported the development of systemic artery lesions in addition to coronary lesions 55 . Together, these observations suggest that in children with KD the incidence of AAA and dilation may be higher than currently appreciated, particularly in infants less than one year of age with very severe KD vasculitis and coronary aneurysms.…”
Section: Discussionmentioning
confidence: 99%
“…The CAWS model shares some histological similarities with human Kawasaki disease pathology in that inflammation affects both the aortic root and the proximal region of the coronary arteries 190 . Inflammation can also affect non-coronary artery sites in 25% of CAWS-injected mice and can be observed in the lymph nodes, the kidneys and the liver 190,192 . CAWS-induced coronary artery lesions resemble those of human Kawasaki disease and are typically proliferative, granulomatous and characterized by intimal thickening with destruction of the elastic lamina and media 190 .…”
Section: Mouse Models Of Kawasaki Diseasementioning
confidence: 99%
“…KD-like vasculitis can be induced in rabbit, swine, and mouse models by various methods (80)(81)(82)(83). The known genetic background and ease of genetic manipulation have made mouse models the preferred model to investigate molecular pathogenesis of KD and to discover its therapeutic targets (84)(85)(86)(87)(88).…”
Section: Insight From Experimental Studies With Animal Model For Kdmentioning
confidence: 99%